Pengaruh Laba Bersih, Arus Kas Operasi dan Persediaan Dalam Memprediksi Arus Kas Masa Mendatang Pada Sektor Industri Dasar dan Kimia di Bei 2018-2020 - Candra Irawan (Journal of Trends Economics and Accounting Research, 2021)
Predicting the future cash flows of a company is a fundamental problem in accounting and finance which reminds that the value of a security firm depends on its ability to generate cash flows. Based on PSAK No. 1 of 2015 states that financial statements are a structured presentation of the financial position and financial performance of an entity. This report displays the history of the entity quantified in monetary value. The results of the study show that net income has a positive and significant effect on future cash flows in the Basic and Chemical Industry sector on the 2018-2020 BEI, operating cash flow has a positive and significant impact on future cash flows in the Basic and Chemical Industry sector on the 2018-2020 BEI, and inventories have a positive and significant impact on future cash flows in the Basic and Chemical Industry sector on the IDX 2018 – 2020